Pregnancy Classes Increase Knowledge of Early Detection of High-Risk of Pregnancy - Kusumaningsih Wurihandayani; Siti Fadhilah; Lia Ayu Kusumawardani (Universitas Islam Jember, 2023)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) in Pacitan Regency, are still quite high. This is related to access, socio-cultural, educational, and economic factors. To prevent more dangerous risks for pregnant women and their fetuses, mothers' knowledge about early detection of pregnancy complications needs to be increased by holding classes for pregnant women. This experience analyzes the effect of pregnant women's class on mothers’ knowledge in the early detection of high-risk pregnancies in the Tanjungsari Health Center area, Pacitan. In this study, the design used was Quasi-Experimental with the One Group Pre-Test and Post-Test Design research design. The sampling technique in this study is Simple Random Sampling. The samples in the study are pregnant women in the I-III trimesters was taken who had never attended a class for pregnant women during pregnancy in November 2022 from 15 villages in Tanjungsari Health Center. Data analysis using the Paired Sample T-Test analysis obtained a test result value = 0.000 ( p-value <0.05). There is an effect of the class of pregnant women on mothers’ knowledge in early detection of high-risk pregnancies